2016
DOI: 10.5923/j.ijme.20160602.06
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Paricá Wood Using Structural Members and Clear Specimens

Abstract: The aim of this research is determining mechanical properties of Paricá wood specie (Schizolobium amazonicum Herb) using structural and clear specimens, according to Brazilian standard ABNT NBR 7190 requirements. Paricá wood specie in structural members, with moisture content of around 12%, were determined dynamic elasticity modulus (transverse vibration tests), static bending modulus (three point bending) and modulus of rupture in static bending test. In clear specimens, according to Brazilian standard were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 9 publications
0
8
0
3
Order By: Relevance
“…Desiring to demonstrate the wood potential, Cavalheiro et al [21] showed that wood Paricá (Schizolobium amazonicum), strength class C20, has good strength properties and therefore has great potential for use in timber structures.…”
Section: Art Statementioning
confidence: 99%
“…Desiring to demonstrate the wood potential, Cavalheiro et al [21] showed that wood Paricá (Schizolobium amazonicum), strength class C20, has good strength properties and therefore has great potential for use in timber structures.…”
Section: Art Statementioning
confidence: 99%
“…This may be related mainly to the origin and age of the trees considered. The MOEs for paricá beams without preservative treatment evaluated by Cavalheiro et al (2016) using the same glue as that used in this work and for beams chemically treated with CCA were 9,150 and 8,764 MPa, respectively. These values are much lower than our findings, as seen in Table 2.…”
Section: Mechanical Properties Of Beamsmentioning
confidence: 93%
“…The average values of untreated beams reported by Terezo & Szücs (2010) for normal tensile and shear parallel to the bonding line were 3.81 and 2.97 MPa, respectively. Cavalheiro et al (2016) reported a 3.40 MPa value for the shear strength parallel to the bonding line. These lower results may be due to the tree planting site and age variability.…”
Section: Bonding Line Strengthmentioning
confidence: 99%
“…Para confecção dos corpos de prova e procedimentos de ensaios para determinação das propriedades físicas e mecânicas, foram seguidas as recomendações do Anexo B "Determinação das Propriedades das Madeiras para Projetos de Estrutura" da norma ABNT NBR 7190 (1997) [18]. Para isso, foram caracterizadas duas duas propriedades físicas e cinco propriedades mecânicas (Tabela 1), sendo fabricados 12 corpos de prova para cada uma, para ambos os lotes.…”
Section: Materiais E Métodosunclassified
“…Esta variabilidade das propriedades da madeira pode estar relacionada com as características inerentes das diferentes espécies e gêneros de árvores que fornecem este material, além disso, por fatores anatômicos, direção das fibras, densidade e teor de umidade [16][17][18][19][20]. O teor de umidade da madeira é de fundamental conhecimento para a estimativa de suas propriedades físicas e mecânicas e para o seu emprego de maneira racional na construção civil.…”
Section: Introductionunclassified